DAMPAK PENGGUNAAN SMARTPHONE TERHADAP KARAKTER RELIGIUS PESERTA DIDIK DI KELAS II DI SDN 21/II RANTAU IKIL KEMATAN JUJUHAN - Lika Apreasta; Yulia Darniyanti; Ela Pertiwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The purpose of this study was to see how the impact of using smartphones, the religious character of students and the efforts of teachers in instilling religious character in students. This study used a qualitative approach with a descriptive research type, the informant selection technique was carried out by means of purposive sampling. Data collection techniques with in-depth interviews, observation, and documentation studies. Data analysis uses the Miles and Huberman models. The results of this study are in accordance with the formulation of the problem (1) the impact of using smartphones on the religious character of students, (2) the efforts of teachers in instilling religious character in students. Based on the formulation of the problem, it can be formulated that the impact of smartphone use greatly influences the religious character of students. As for the impact of using a smartphone, namely (a) likes to rebel or fight, (b) lack of interest in learning, (c) lazy to pray, (d) arrogant, (e) likes to be alone. These efforts were carried out by the teachers to shape the personality of students to be better, and have good character as well.